Single institution experience with telemedicine for pediatric urology outpatient visits: Adapting to COVID-19 restrictions, patient satisfaction, and future utilization. Issue 4 (August 2021) - Gan, Zoe; Lee, Seo Young; Weiss, Dana A.; Van Batavia, Jason; Siu, Sharmayne; Frazier, Jennifer; Zderic, Stephen A.; Shukla, Aseem R.; Srinivasan, Arun K.; Kolon, Thomas F.; Zaontz, Mark R.; Canning, Douglas A.; et al.
Summary: Introduction: Widespread utilization of telemedicine in our practice to date has been limited to the evaluation of certain post-surgical patients. The COVID-19 pandemic acutely stressed our established system and required us to enhance our utilization of telemedicine. We hypothesized that expansion of telemedicine to new and follow up patient visits for pediatric urology could be done effectively in a way that satisfied patient and parental expectations. Materials and methods: Using a pre-COVID-19 established telemedicine program based in our electronic medical record (EMR), patients and providers transitioned to primarily virtual visits when clinically appropriate. Guidelines were formulated to direct patient scheduling, provider and staff education was provided, including a process map designed for multiple providers to complete video visits (VV), and the EMR was redesigned to incorporate telehealth terminology. The number of VV per provider was recorded using the electronic medical record, and patient reported outcomes (PRO) were measured using a standardized questionnaire. Results: A total of 631 VV met inclusion criteria during the period of May 2018–April 2020. This included 334 follow up, 172 new, and 125 postoperative visits. The median age of patients at time of visit was 7 years (IQR 2–12 years), median visit time was 20 min (IQR 15–30 min), and the median travel distance saved by performing a VV was 12.2 miles (IQR 6.3–26.8 miles). Diagnoses were varied and included the entire breadth of a standard pediatric urology practice. The PRO questionnaire was completed for 325 of those patient visits. Families reported a high overall satisfaction with the video visits (median score of 10 out of 10) and felt that the visit met their child's medical needs. 90% stated that they would strongly recommend a telehealth visit to other families. Patients and parents reported benefits of VV including decreased travel costs and less time taken off from work and school. Conclusion: The EMR enabled nimble redirection of clinical care in the setting of a global pandemic. The enhanced use of telemedicine has proved to be an alternative method to provide care for pediatric urology patients. Families indicate a high degree of satisfaction with this technology in addition to significant time and cost savings. Telemedicine should remain a key aspect of medical care and expanded from post-operative visits to new patient and follow up visits, even as we return to our normal practices as the pandemic restrictions soften. Summary figure Program map depicting the sequence of a video visit (VV). The process begins with our scheduling team which provides the necessary information to the family and ensures that they can be scheduled properly. The family is encouraged to conduct the visit in a quiet place with at least one parent and the child present. Relevant records, imaging, and laboratory studies should be uploaded prior to the visit. In addition, pictures and/or videos uploaded by the family prior to the visit can facilitate the examination portion of the visit. VV = video visit; AVS = after visit summary. Summary figure